Optimization of a nitrogen fertilizer application scheme for spring maize in full-film double-ridge furrow in Longzhong, China - Liu, Yu; Li, Shilei; Liu, Yanxin; Shen, Hongzheng; Huang, Tingting; Ma, Xiaoyi (Agricultural water management, 2023)
Full-film double-ridge furrow sowing technology (FDRFST) and nitrogen (N) management are crucial for sustainable agricultural development. To investigate the N fertilizer application scheme for spring maize with high yield, precipitation water productivity (PWP), and N use efficiency (NUE) under the FDRFST, a two-year field experiment was carried out in a rainfed area of Longzhong (LZ). Treatments included two types of N fertilization (common urea [U] and controlled release urea [CU]), three application rates (180, 225, and 270 kg hm⁻²), and the conditions of no N fertilizer application and no plastic film mulching. The results showed that the temperature-increase effect of PM on the soil between 2021 and 2022 was concentrated for 0–90 days, with average values of the 5 cm soil temperature increasing by 4.15 and 3.58 ºC, respectively. However, the N fertilizer application rate had negligible effects on soil temperature. Plastic film mulching (PM) required temperature-increase compensation, particularly during the sowing–emergence stage, with a 1.68 compensation coefficient. Based on the simulation results of the modified DNDC model, the recommended application rate of CU (180 kg hm⁻²) for spring maize in LZ increased the average yield, PWP, and NUE by 15.8%, 16.0%, and 36.4% from 1981 to 2020, respectively, compared to U treatments. Our results provide a theoretical basis for N management in spring maize production in LZ and offer critical insights for improving the DNDC model under PM conditions.